Parental knowledge and care-seeking practices towards pediatric ear infections: a study from Iraq - Aqil Mohammad Daher; Abdulla Alnakshabandi; Khaled Hashim Sultan; Basim A.Al-Abdely; Allya Mohammad Ali (Intelektual Pustaka Media Utama, 2022)
An ear infection (EI) is one of the most common pediatric illnesses. This study aimed to assess parental knowledge, care-seeking practices, and factors associated with them. A cross-sectional study involved a sample of parents attending hospitals in three selected cities in Iraq. Data were collected with a questionnaire composed of three parts: i) Sociodemographic characteristics, ii) Questions related to knowledge of symptoms, risk factors, and complications of an EI, and iii) Questions related to care-seeking practices. The mean age of respondents was 34.99 (±9.85) years. Females made up 58.90% of the sample. More than half reported holding tertiary education. Most participants showed satisfactory knowledge of EI symptoms (88.10%) and proper practices of seeking medical attention from a doctor or other medic (95.80%). Respondents with tertiary education had higher odds of having satisfactory knowledge (OR 4.63, 95% CI 1.18-18.19) and proper care-seeking practices (OR 14.96, 95% CI 1.12-28.80) than those with primary education and below. Current smokers had higher odds of having unsatisfactory knowledge (OR 0.12, 95% CI 0.02-0.70) than non-smokers. In conclusion, respondents had sufficient knowledge and care-seeking practices. Educational level was associated with adequate knowledge and care-seeking practices, and former smoking status was associated with unsatisfactory knowledge.